2016
DOI: 10.1111/maps.12618
|View full text |Cite
|
Sign up to set email alerts
|

Major and trace element geochemistry of S‐type cosmic spherules

Abstract: Abstract-Micrometeorites that pass through the Earth's atmosphere undergo changes in their chemical compositions, thereby making it difficult to understand if they are sourced from the matrix, chondrules, or calcium-aluminum-rich inclusions (CAIs). These components have the potential to provide evidence toward the understanding of the early solar nebular evolution. The variations in the major element and trace element compositions of 155 different type (scoriaceous, relict bearing, porphyritic, barred, cryptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…As atmospheric melting and concomitant evaporation experienced by CSs strongly affected primary textures, mineralogy and chemical compositions, precisely constraining the nature of the chondritic sources remains highly challenging (e.g., Alexander et al, 2002;Taylor et al, 2005). Most elemental concentrations and ratios are either not sufficiently discriminative or underwent too large a modification to deduce the type of precursor body (e.g., Rudraswami et al, 2016).…”
Section: Constraints From Elemental Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…As atmospheric melting and concomitant evaporation experienced by CSs strongly affected primary textures, mineralogy and chemical compositions, precisely constraining the nature of the chondritic sources remains highly challenging (e.g., Alexander et al, 2002;Taylor et al, 2005). Most elemental concentrations and ratios are either not sufficiently discriminative or underwent too large a modification to deduce the type of precursor body (e.g., Rudraswami et al, 2016).…”
Section: Constraints From Elemental Chemistrymentioning
confidence: 99%
“…Due to different production mechanisms in and transportation pathways from their source regions, these microscopic particles sample parent bodies different from those of meteorites (e.g., Fredriksson and Martin, 1963;Ganapathy et al, 1978;Engrand and Maurette, 1998;Flynn et al, 2009;Gounelle et al, 2009;Dartois et al, 2013;Cordier and Folco, 2014;Rubin, 2018). Generally recovered from deep-sea sediments, seasonal lakes in Greenland, ice and snow in Greenland and Antarctica, Antarctic moraines, continental sands and soils, and more recently also urban environments (e.g., Brownlee et al, 1979;Blanchard et al, 1980;Koeberl and Hagen, 1989;Hagen et al, 1989;Engrand and Maurette, 1998;Taylor and Lever, 2001;Genge et al, 2016Genge et al, , 2017Rudraswami et al, 2016;van Ginneken et al, 2017), MMs have also been found concentrated in high-altitude sedimentary traps, i.e., a pits, fissures and cracks of glacially eroded surfaces, in the Transantarctic Mountains (TAM) (e.g., Rochette et al, 2008;Suavet et al, 2009). To concentrate MMs in numbers sufficient to be able to efficiently distinguish them from terrestrial particles in sedimentary deposits, the accumulation time of such traps is ideally of the order of millions of years, while at the same time alteration must have remained limited, with minimal background or anthropogenic contributions (Suavet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmic spherules from deep‐sea sediments, namely AAS38‐164‐P69 and AAS62‐9‐P51, also revealed spinels contained in them (Rudraswami et al. ). Spinel is the refractory mineral that is frequently found in CAIs of CM or CV chondrites, but forms a small fraction of these meteorites: ~1.2 and ~3 area% of refractory inclusions, respectively (Hezel et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Rudraswami et al. , ), in addition to oxygen isotope studies on different types of MMs (Engrand et al. , ; Yada et al.…”
Section: Introductionmentioning
confidence: 99%